A Taxonomic & Ecological Study of the fossils of Selected areas of the marshes of Sothern Iraq - Rasha Abdel-Sattar Kechiche Al-Ali /Sura Asaad Saleem Alshuraida ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The study was conducted in the southern part of the marshes of Iraq, specifically in the north of Basra governorate, starting from the marshes of northern Basra and ending with the marshes of the Nasiriya border area (Gerbisi). In this study, (7 sites) were identified for taking samples for portholes with a depth of (1 meter) (4) and surface samples with a depth of (20 cm) (17 samples) starting from the north of Rumelia to the borders of Nasiriya And then the stage of laboratory work begins, where the fossils were sorted from the non-solidified sediments by the sorting method, where a part of the original sample 50 g was taken and placed in a glass container (Beaker) to obtain the required results. Several diverse life groups were found, including about 19 species Foraminifera and about 12 species of Ostracoda and 18 types of shellfish. DOI /10.54633/2333-021-042-032